SERVICE QUALITY OF WELFARE SERVICES AND STUDENTS’ SATISFACTION IN NIGERIAN FEDERAL UNIVERSITIES - Ayotunde Akinwale; Rashidat Ibrahim; Sina Ayelabowo; Leycot Anyanwu (IJIET (International Journal of Indonesian Education and Teaching), 2025)
This study determined the impact of Service Tangibility of welfare services, Service Reliability of welfare services, Service Responsiveness of welfare services, Service Empathy of welfare services, and Service Assurance of welfare services on the satisfaction of students in federal universities in South West Nigeria. The design for the study was descriptive correlational research design using quantitative approach. The study population was 193,526 students while the study sample was 1,144 students. The sample was drawn from three universities in South West Nigeria. The instrument for the study was tagged ‘Students’ Satisfaction and Service Quality Questionnaire (SSSQQ). Hypotheses for the study were tested using Pearson Product Moment Correlation ( PPMC). The results indicated that Service Tangibility of welfare services had significant impact (r=0.758; p0.01) on students’ satisfaction. Furthermore, Service Reliability of welfare services had significant impact (r=0.635; p0.01) on students’ satisfaction. Also, Service Responsiveness of welfare services had significant impact (r=0.518; p0.01) on students’ satisfaction. Similarly, Service Empathy of welfare services had significant impact (r=0.692; p0.01) on students’ satisfaction. In addition, Service Assurance of welfare services had significant impact (r=0.532; p0.01) on students’ satisfaction. The study concluded that the level quality of welfare services affect the satisfaction of students in the study areas. The study recommended improvement in the quality of welfare services for improved students' satisfaction